New-Onset Tongue Weakness Due to Skull Base Metastases to Bilateral Hypoglossal Canals - Michael T. Do; Tony Dong; Soheil El-Azzouni; Bahar Moftakhar (Annals of Internal Medicine: Clinical Cases)
Hypoglossal nerve palsy is a rare disorder resulting in dysarthria and tongue weakness, usually caused by direct nerve compression or injury. Malignant invasion of the skull base can rarely lead to bilateral hypoglossal nerve compression at the exit of the hypoglossal canals. We report the case of a 40-year-old man with stage IV colorectal cancer who presented with tongue weakness and dysphagia and was discovered to have new metastases to his skull base with invasion of his bilateral hypoglossal canals.